Physiotherapy students' perceptions and experiences of clinical prediction rules. Issue 3 (September 2017) - Knox, Grahame M.; Snodgrass, Suzanne J.; Stanton, Tasha R.; Kelly, David H.; Vicenzino, Bill; Wand, Benedict M.; Rivett, Darren A.
Abstract: Objectives: Clinical reasoning can be difficult to teach to pre-professional physiotherapy students due to their lack of clinical experience. It may be that tools such as clinical prediction rules (CPRs) could aid the process, but there has been little investigation into their use in physiotherapy clinical education. This study aimed to determine the perceptions and experiences of physiotherapy students regarding CPRs, and whether they are learning about CPRs on clinical placement. Design: Cross-sectional survey using a paper-based questionnaire. Participants: Final year pre-professional physiotherapy students ( n  = 371, response rate 77%) from five universities across five states of Australia. Results: Sixty percent of respondents had not heard of CPRs, and a further 19% had not clinically used CPRs. Only 21% reported using CPRs, and of these nearly three-quarters were rarely, if ever, learning about CPRs in the clinical setting. However most of those who used CPRs (78%) believed CPRs assisted in the development of clinical reasoning skills and none (0%) was opposed to the teaching of CPRs to students. The CPRs most commonly recognised and used by students were those for determining the need for an X-ray following injuries to the ankle and foot (67%), and for identifying deep venous thrombosis (63%). Conclusions: The large majority of students in this sample knew little, if anything, about CPRs and few had learned about, experienced or practiced them on clinical placement. However, students who were aware of CPRs found them helpful for their clinical reasoning and were in favour of learning more about them.